Carbon nanotube supported ruthenium catalysts for the treatment of high strength wastewater with aniline using wet air oxidation - García, Juan (2008)
Multi-walled carbon nanotubes (MWCNT) can be efficiently used as support of ruthenium catalysts for the catalytic wet air oxidation of high strength wastewater containing aniline. Catalysts were prepared using different ruthenium precursors, Ruthenocene [Ru(g5-C5H52], Ruthenium (1,5-cyclooctadiene, 1,3,5-cyclooctatriene) [Ru(cod)(cot)] and Ruthenium trichloride (RuCl3.xH2O), different impregnation methods (excess solution and incipient wetness impregnation) and different MWCNT support surface chemistry (nitric acid oxidized MWCNT-COOH and Na2CO3 ion exchanged MWCNT-COONa). The efficiency of the aniline removal obtained with the catalysts prepared with different precursors decreases in the order [Ru(cod)(cot)] > RuCl3.xH2O > [Ru(g5-C5H52], 100% aniline conversion being obtained after 45 min of reaction with the catalyst prepared with [Ru(cod)(cot)]. The influence of the impregnation technique was found to be negligible, while the use of the MWCNT-COONa support led to increased catalyst performances when compared to that obtained with catalysts prepared with the MWCNT-COOH support. Leaching of ruthenium was observed in all cases, but the use of the precursor [Ru(cod)(cot)] and of the support MWCNT-COONa in the preparation of the catalysts seems to improve their stability. A direct relationship between metal load and catalyst stability was found and attributed to the strength of metal-support interactions.